2020
DOI: 10.1183/13993003.00950-2019
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient genome editing in primary human bronchial epithelial cells differentiated at air–liquid interface

Abstract: The structure and composition of the bronchial epithelium is altered in respiratory diseases such as COPD and asthma, in which goblet cell hyperplasia and reduced numbers of ciliated cells impair mucociliary clearance. We describe a robust genome editing pipeline to interrogate modulators of primary human bronchial epithelial cell (HBEC) differentiation and function. By employing plasmid-and virus-free delivery of CRISPR/Cas9 to human airway basal cells we achieve highly efficient gene inactivation without the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…CRISPR knockout mutations were generated as described ( 71 ) with slight modifications. Specifically, individual single guide RNAs (sgRNAs) and Cas9 Electroporation Enhancer (IDT, 1075916) were each resuspended at 100 μM in nuclease-free duplex buffer (IDT, 11-01-03-01).…”
Section: Methodsmentioning
confidence: 99%
“…CRISPR knockout mutations were generated as described ( 71 ) with slight modifications. Specifically, individual single guide RNAs (sgRNAs) and Cas9 Electroporation Enhancer (IDT, 1075916) were each resuspended at 100 μM in nuclease-free duplex buffer (IDT, 11-01-03-01).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have reported the use of lipid-mediated reverse-transfection at the time of plating HBEs and before differentiation of ALIs (9), although there are reports showing resistance of ALI cultures to lipid-mediated small interfering RNA (siRNA) knockdown (10), whereas others have shown $30% siRNA knockdown in ALIs using nanoparticle-mediated delivery (11). In addition, CRISPR/Cas9 has been tested for gene silencing in HBEs before ALI cultures (12,13), but cost, target design, and experimental design limitations can pose problems for some investigators.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, gene editing can be performed once airway cells have differentiated in ALI cultures (105).…”
Section: Modelling Disease Initiation and Pathogenesismentioning
confidence: 99%